A REVIEW UPDATED ON ETHNOPHARMACOLOGICAL PROFILE OF KIRGANELIA RETICULATA POIR (BAILL). : AN IMPORTANT HERBAL PLANT - Soni, Rajesh Kumar; Dixit, Vihangesh; Singh, Harsh; Irchhaiya, Raghuveer; Yadav, Prayag (Journal of Drug Delivery and Therapeutics, 2014)
Kirganelia reticulata (Poir.) Baill. is known for its importance in various traditional medicines around the world. In present review covers a literature survey across from 1971 to 2014 until now. The some information collected from published literature on species of Kirganelia reticulata (Poir.) Baill. (=Syn. Phyllanthus reticulatus Poir.).The extract and the compounds isolated from Kirganelia reticulata show a wide spectrum of biological activities including antidiabetic, antibacterial, antioxidant, hepatoprotective, antiplasmodial, anticiceptive, analgesic and anti-inflammatory properties.